If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + -3f = 2f Solving 22 + -3f = 2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2f' to each side of the equation. 22 + -3f + -2f = 2f + -2f Combine like terms: -3f + -2f = -5f 22 + -5f = 2f + -2f Combine like terms: 2f + -2f = 0 22 + -5f = 0 Add '-22' to each side of the equation. 22 + -22 + -5f = 0 + -22 Combine like terms: 22 + -22 = 0 0 + -5f = 0 + -22 -5f = 0 + -22 Combine like terms: 0 + -22 = -22 -5f = -22 Divide each side by '-5'. f = 4.4 Simplifying f = 4.4
| 9y^2-24+11=0 | | t=14-2t | | 4t=15-13t | | x^3+3x^2-24x-3=0 | | 7n+26=5n | | 6.1+10.1q=4q | | 13p+54=7p | | 3x^3-15x^2+21x-5=0 | | 0.3c=25.9+4c | | 8.4d-23=13d | | 71-12=9a | | 4x-6=7x+3 | | x-(a+3)=a-2(a-x) | | 192-7x=29x+16 | | x^8-6x^6=0 | | 11-9x=128-30x | | 223+175= | | 123+175= | | x^4+2x^3+x^2=0 | | -15-6x=5-10x | | 5x-7=2x+3x-7 | | 4x^2=36x | | 490-x=23 | | 2h+3h^2-2h^3=2 | | 2h+3h^2-2h^3=3 | | -5x=8 | | 8g=5g-21 | | 17a=4a-9 | | 3g+17.2=11.6g | | 49-3x=6x+19 | | 5n=53-2.6n | | 6p=60-4p |